Non-normality and risk in developing Asian markets - Alles, Lakshman; Murray, L. (World Scientific Publishing Co. Pte. Ltd., 2010)
This paper examines whether additional risk factors such as the variance, skewness, and coskewness of returns offer an appropriate explanation of company returns in less developed capital markets. Arguments for considering some additional factors in pricing models to better deal with such situations are presented. Using individual company returns from a range of developing Asian capital markets, empirical tests examine the importance of these extra risk factors. Results indicate that both individually and when in combination, variance and coskewness are significantly related to returns in these markets. Skewness is less consistently important. Robustness tests confirm that these measures tend not to capture size or book to market factors.